Quantitative analysis of the age structured mathematical model of varicella spread in Slovakia - Zibolenová, Jana; Ševčovič, Daniel; Baška, Tibor; Hudečková, Henrieta (Proceedings of the Conference Algoritmy, 2016)
Varicella (chickenpox) is one of the most frequent infectious diseases in childhood. The aim of this work is to describe the incidence and susceptibility to varicella in Slovak population using the age-structured SIR (Susceptible - Infected - Recovered) model. The model was calibrated to estimate disease incidence in the Slovak population. Sensitivity analysis of transmission parameters and initial conditions were performed. This model is appropriate to describe the spread of disease and susceptibility of a large population in separate age groups.